Growing three-dimensional biomorphic graphene powders using naturally abundant diatomite templates towards high solution processability - Ke Chen (Nature Portfolio, 2016)
High-volume, low-cost production of graphene is pivotal for the industrial advance of this 2D material. Here, the authors make use of naturally occurring diatomite as a 3D substrate for graphene growth, obtaining non-planar porous graphene structures after removal of the silica templates.